Implementasi dan Analisis User Interface pada Website The Room 19 sebagai Perpustakaan Independen di Kota Bandung - Rochmawati, Irma; Luqman, Ria Fathya; Yunus, Syarip; Cahyadi, Arif Try (Visualita Jurnal Online Desain Komunikasi Visual, 2025)
The Room 19 is an independent library space located in Bandung with a cafe library concept. Currently, The Room 19 provides information related to the place and facilities through its website and social media. However, The Room 19's website design looks simple and does not display complete information. A website design can be said to have successfully run according to plan or has fulfilled the wishes of the user, one of which depends on the application of the user interface. With clear planning and analysis, it can minimize problems in the process of developing a website. This research aims to provide an overview of the implementation of user interfaces using the prototyping method on web pages as an initial step in digital media development activities. The purpose of making this prototype is to provide a common perception and understanding of the basic user interface process in developing a website, so that there is good communication between developers and system users. The results of this research can be used as a reference or reference for website design developers who have followed the prototyping steps in a structured manner, thus providing an overview of the process for users and observers of website design development science.